Scientific Literacy-Based Flipped Classroom Virtual Strategy for Biology Learning in the New Normal Era - Ridlo, S.; Marina, H.; Sapitri, D.; Hadiyanti, L. N.; Listyono, L. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Various research results concerned with flipped classrooms reported to mandate more benefits to form a positive attitude, self-efficacy, and self-regulated learning and affect students' abilities and skills. This research, which involved three studies, aims to develop a flipped classroom strategy model for virtual biology learning. The research was conducted in three high schools and the Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang, at the beginning of the new normal habit of the COVID-19 pandemic. The analysis results of study 1 were applied in designing study 2, and the results of study 2 were applied to develop the model in study 3. The results showed that the flipped strategy was proven to improve skills employing information technology to benefit learning and student participation. The flipped strategy is proven to have better effects on learning outcomes and students' self-efficacy. The strategy model, arranged with asynchronous-synchronous-asynchronous in scientific literacy-based learning syntax and practiced with flipped e-learning instructions, is an ideal flipped classroom model. It is well appreciated by validators, teachers, and students and has proven to function well.